2016
DOI: 10.1177/1087054716629213
|View full text |Cite
|
Sign up to set email alerts
|

Amygdala Abnormalities in Adults With ADHD

Abstract: Patients with ADHD tend to have smaller amygdala volumes. ADHD patients presented less activation in the area of the left frontal pole than the controls. There was no amygdala activation stated when presenting the pleasant images. Whereas bigger activation of the left amygdala was found in patients while presenting them unpleasant images. These results might suggest that lower emotional processing and less control of impulsivity is associated with dysfunctional amygdala in ADHD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 42 publications
1
19
0
1
Order By: Relevance
“…At another locus, TMEM161B, a transmembrane protein, had the highest posterior inclusion probability of 0.838 in the amygdala. Brain imaging studies have shown that the amygdala has decreased volume in ADHD patients 15 . Genetic variants in the gene have also been previously associated with major depressive disorder (MDD), which is a disorder that is often co-morbid with ADHD 16 .…”
Section: Discussionmentioning
confidence: 99%
“…At another locus, TMEM161B, a transmembrane protein, had the highest posterior inclusion probability of 0.838 in the amygdala. Brain imaging studies have shown that the amygdala has decreased volume in ADHD patients 15 . Genetic variants in the gene have also been previously associated with major depressive disorder (MDD), which is a disorder that is often co-morbid with ADHD 16 .…”
Section: Discussionmentioning
confidence: 99%
“…The amygdala and associated circuitry have been primarily related to avoidance mechanisms, and the striatum and associated circuitry to approach mechanisms (Ernst and Fudge, 2009). Furthermore, amygdala and striatum abnormalities have been associated with different psychiatric problem domains, for example with depression (Stuhrmann et al, 2011), (social) anxiety (Shin and Liberzon, 2009; Freitas-Ferrari et al, 2010), avoidance behavior (Schlund et al, 2013), ADHD (Cubillo et al, 2012; Tajima-Pozo et al, 2016) and antisocial behavior (Glenn and Yang, 2012; Blair, 2013). To further link approach and reward mechanisms to facial emotion processing in the specific psychiatric problem domains, we commend future study of activation and connectivity of the amygdala, striatum and their associated circuits during the processing of conscious as well as subliminally presented facial emotions.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of amygdala anatomical abnormities in children with ADHD were supported by many previous studies. Amygdala played as a critically important role in emotion regulation (Banks et al, 2007; Davidson et al, 2000; Domes et al, 2010) and thus structural anomalies associated amygdala have been widely observed in children (Van Dessel et al, 2019) and adults with ADHD (Tajima-Pozo et al, 2018), which suggested that the aberrant structure of amygdala may be associated with less control of impulsivity and delay aversion (Van Dessel et al, 2018).…”
Section: Discussionmentioning
confidence: 99%